On Becoming a Leader - Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Diversity & Cultural Competence - Labas, G; Gregory, J.L. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Research and Program Evaluation - Haynes, N.M.; Gregory, J.L.; Diffley, W.J. (Educational Leadership: Perspectives on Preparation and Practice, 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedag...
Keywords: dept.edl

Educational Leadership: Perspectives on Preparation and Practice - Haynes, Norris M.; Arafeh, Sousan; Magagula, Cynthia McDaniels (University Press of America, ® Inc., 2015)
This book identifies core knowledge that educational leaders need to learn in pre-service preparation and throughout in-service professional development. The contributors discuss established pedagogical and experiential learning models as well as provocative new paradigms of their own to help prepare leaders and reinforce leadership effectiveness.
Keywords: Educational leadership; School management and organization; dept.edl; faculty_collection